From the Balkans to France: the threatened range-restricted freshwater mussel Unio carneus revealed as an introduced species by environmental DNA - Vincent Prie; Luc Clement; Coline Gaboriaud; Miguel Gailledrat; David Naudon; Rémi Bourru; Manuel Lopes-Lima; Alice Valentini (Biological Invasions, 2026)
Environmental DNA (eDNA) is a powerful, non-invasive tool for detecting invasive species at an early stage, even when populations are small or elusive. Its high sensitivity can reveal introductions that might otherwise go unnoticed for decades. Large-scale eDNA surveys of freshwater bivalves across French rivers uncovered the presence of Unio carneus , a mussel species endemic to the Drin Basin in the Balkans and threatened in its native range. Identification was confirmed through genetic analysis of live specimens. In France, the distribution of U. carneus largely overlaps with that of the Albanian roach Pachychilon pictum , a fish introduced from the same region in the late 1980s, suggesting introduction via parasitic larvae on its host. However, detections outside the fish’s known range raise questions about alternative hosts and the mussel’s ability to adapt to local conditions. The French population shows low genetic diversity, consistent with a founder effect, and appears to be of low invasiveness to date. This case illustrates the value of eDNA for uncovering overlooked introductions and highlights the conservation paradox posed by species that are threatened in their native range yet may act as emerging invaders elsewhere.